2021
DOI: 10.1161/str.52.suppl_1.p132
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P132: Successful Conduct of an Acute Stroke Clinical Trial During COVID

Abstract: Introduction: Most clinical research stopped during COVID due to possible impact on data quality and personnel safety. We aimed to assess the impact of COVID on study conduct at sites that continued to enroll patients during the pandemic. Methods: BEST-MSU is an ongoing study of Mobile Stroke Units (MSU) vs standard management of tPA eligible acute stroke patients in the pre-hospital setting. MSU personnel include a vascular neurologist via telemedicine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These units provide timely and efficient stroke care to patients by bringing the expertise and resources of the hospital directly to the patient's location. The use of MSUs has been shown to reduce the alarm-to-treatment time (ATT), increase the number of patients treated in the first hour after symptom onset, and improve functional outcomes compared to regular care (3)(4)(5)(6)(7)(8)(9)(10). In Berlin, MSUs have been in operation since 2011 as special vehicles of the Berlin Fire Department (Stroke Emergency Mobiles, STEMO).…”
Section: Introductionmentioning
confidence: 99%
“…These units provide timely and efficient stroke care to patients by bringing the expertise and resources of the hospital directly to the patient's location. The use of MSUs has been shown to reduce the alarm-to-treatment time (ATT), increase the number of patients treated in the first hour after symptom onset, and improve functional outcomes compared to regular care (3)(4)(5)(6)(7)(8)(9)(10). In Berlin, MSUs have been in operation since 2011 as special vehicles of the Berlin Fire Department (Stroke Emergency Mobiles, STEMO).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile stroke units (MSUs)-ambulances with a CT scanner and a point-of-care (POC) laboratory on board-significantly reduce the alarm-to-treatment time (ATT) compared to regular care and increase the number of patients treated within 60 min after the onset of symptoms (11)(12)(13)(14), two large studies (Berlin_PRehospital Or Usual Delivery of Acute Stroke Care (B_PROUD) and BEnefits of Stroke Treatment Delivered Using a Mobile Stroke Unit [BEST-MSU]) independently demonstrated that treatment on board an MSU led to a significant reduction in disability at 90 days (15,16). Furthermore, in cases of large vessel occlusion (LVO), patients can be selectively transported to the next appropriate hospital offering mechanical thrombectomy.…”
Section: Introductionmentioning
confidence: 99%